Penanggulangan Premanisme Di Kota Medan (Studi di Satuan Reskrim Polresta Medan) - Berlin Sinaga; Triono Eddy; Tengku Erwinsyahbana (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
Thuggery is the activity of a group of people who earn their income mainly from extortion of other groups of people and cause public unrest. In Medan City until now thuggery continues to grow and is very detrimental to the community. The purpose of this study was to examine the factors associated with thuggery in Medan, the efforts to overcome them, and the obstacles experienced by the Medan Police Criminal Investigation Unit in overcoming thuggery acts. The research conducted was an empirical juridical research which was sourced from primary data by conducting interviews with AKP Heri Sofian who served as Padal OPS of the Medan Police Criminal Investigation Unit's Preman Hunting Team and secondary data by processing data from primary legal materials, secondary legal materials and tertiary legal materials. The results of the study show that there are many factors that influence the occurrence of thuggery in Medan, both in terms of criminology, it is found that someone becomes a thug due to lack of education, laziness to work and the emergence of a wrong mindset that being a thug is something great and should be proud of, apart from that the factors the economy also affects because of the poverty experienced by the perpetrator, the last is environmental factors that are not good so that they form a person to become a thug.